INFLUENCE OF STRUCTURE FORMATION PROCESSES ON THE PHYSICAL AND MECHANICAL PROPERTIES OF LAYERS FROM LARGE DESTRUCTIVE SOILS REINFORCED WITH CEMENT - Сєдов, Андрій; Фоменко, Олена (SWorldJournal, 2023)
The work examines the issue of using local low-strength stone materials, strengthened with inorganic binders, in the construction of road clothing. The structural layer made of reinforced material, due to its monolithicity and strength, works in an elasti